Demokratisasi Pendidikan Islam dalam Kearifan Lokal Dayak Hapakat Basara dan Korelasinya dengan Alquran - Neneng Rumsiti (Universitas Pesantren Tinggi Darul 'Ulum, 2022)
The urgency of equal distribution of education is a big challenge to be realized. One of the steps taken is to promote the democratization of education. A more specific scope is, for example, in the learning process that upholds equality of rights without any distinction. This study explores deeper related to the concept of democratization of Islamic education contained in the local wisdom of the Dayak hapakat basara in collaboration with the content of the Qur’ān, 3:159 is related to democratic values, namely the principle of deliberation. The type of research used is qualitative with a concept analysis approach. The concept in question is the democratization of education contained in hapakat basara and the Qur’ān. The results of this study indicate that (1) the values contained in the local wisdom of hapakat basara include the values of unity, peace, and humanity which are realized through a deliberation system by looking for a common solution to the problems faced; (2) in line with this, the Qur’ān, 3:159 also upholds the values of deliberation in resolving all matters as stated in the snippet of verse 159 wa-shāwirhum fī al-amr; (3) the concept of this deliberation which was later adopted and adopted as a concept of democratization of Islamic education resulted in three things, namely in the learning process there must be an agreement between teachers and students, upholding the principle of justice, and prioritizing freedom of opinion as a characteristic of democratic learning.